COVID-19 related knowledge, anxiety, depression and physical activity among Iranian people with relapsing-remitting multiple sclerosis during COVID-19 pandemic: an online cross-sectional survey. - ShahAli, Shabnam; Choobsaz, Haniyeh; Ebrahimi, Reyhane (European Journal of Physiotherapy, 2023)
To determine COVID-19 related knowledge, assess the anxiety/depression and physical activity and their association with demographic variables among Iranian people with relapsing-remitting multiple sclerosis (MS) during the COVID-19 pandemic. It also attempted to find the association between COVID-19 related knowledge and physical activity with anxiety and depression. One hundred and forty MS patients participated in an online cross-sectional survey. The survey, including the COVID-19 related knowledge questionnaire, hospital anxiety, depression scale and International Physical Activity Questionnaire, was carried out through Google forms. Most of the participants had an appropriate level of knowledge regarding COVID-19 (achieved more than 70% of the total score). More than 40% of participants experienced anxiety, depression and more than 50% were lowly active during COVID-19 pandemic. Participants with higher education levels had higher knowledge, physical activity scores and lower anxiety, depression level. Younger participants were more physically active. A negative association between patients' knowledge, physical activity and the symptoms of anxiety, depression was found. Despite the appropriate level of knowledge, it is recommended to provide updated information regarding COVID-19 to ensure MS patients' safety during the pandemic. In addition, the results emphasise the need to implement appropriate strategies to improve physical and mental health.